ADVANCING NATIONAL SOCIO-ECONOMIC DEVELOPMENT AND HEALTH CARE THROUGH WOMEN EDUCATION: IMPLICATIONS FOR COUNSELLING. - Omoniyi, Mary Banke Iyabo (Advances in Social Sciences Research Journal, 2016)
Every society considers the education sector as a necessary indicator of economic, social and health advancement. Moreover, in a nation fraught with poverty, hunger, illiteracy and diseases, education is one of the few weapons that can contribute to meaningful improvement in people’s lives. Nigeria women seem to carry a disproportionate burden of poverty and landlessness that permeates developing societies so that any significant improvement in their role via education can have an important impact on breaking the vicious cycle of poverty and inadequate healthcare currently affecting the nation. Increased women education would not only increase productivity in the fields but also result in greater labour force, lower fertility and mortality rates and improved child health and nutrition which result leads to multiplier effects on the quality of a nation’s resources. Women’s education increases the equitability of the distribution of national wealth and opportunities for citizens regardless of gender. Women seem to be the pulse of the society just as the household is the index of a nation’s wellbeing. A nation that fails to educate her women is running a marathon with one leg and may not go far. This paper focuses on women education and its significance for national socioeconomic development and health care. It also brings out some impediments, obstacles and barriers confronting women education. Thereafter counseling implications were geared towards the need to explicitly address and eradicate persistent gender stereotypes which hinder women from fully utilizing their potentials in national development. Keywords: - Women, Education, Socioeconomic Development, Healthcare, Counselling Implications.